Blind decoding method for a multi-cell massive antenna array system - Binbin YAN; Lei SHEN; Xianyang JIANG; Yu HAN (Dianxin kexue)
In order to overcome the pilot contamination and reduction of decoding performance resulted by neighbouring cell pilot sequences reuse in multi-cell massive array MIMO system，a blind decoding method based on ICA was proposed.The proposed blind decoding method used ICA to separate the received signals of multi-cell users without using pilot sequences.Thus，pilot contamination was avoided and decoding performance would be optimized.Every user’s angle-of-arrival（AOA）was estimated for recognizing the desired user signals and overcoming the uncertainty of signals separated by ICA.The analytical performance and numerical results show that the proposed method has a better performance compared to MMSE decoding and blind decoding method based on singular value decomposition（SVD）.